2021
DOI: 10.30773/pi.2020.0277
|View full text |Cite
|
Sign up to set email alerts
|

The Gender-Sensitive Social Risk Factors for Internet Addiction in College Undergraduate Students

Abstract: Objective The current study aims to explore precipitating and social risk factors for internet addiction (IA) in university undergraduate students, and to provide evidence for interventions and the early prevention of IA in different genders.Methods Four thousand eight hundred and fifty-eight college sophomores completed an online survey on their internet use-related behaviours and social risk factors.Results We found that more male (8.3%) than female students (5.4%) had moderate and severe IA. The main online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 47 publications
2
18
1
Order By: Relevance
“…Nevertheless, such a result occurs less frequently in studies. According to Lin et al ( 36 ), the main online activity among college students with moderate and severe internet addiction was online gaming for males and online streaming for females. Having roommates who engage in similar internet entertainment was a risk factor for internet addiction only for males, while the absence of a romantic relationship was a risk factor for internet addiction only for females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, such a result occurs less frequently in studies. According to Lin et al ( 36 ), the main online activity among college students with moderate and severe internet addiction was online gaming for males and online streaming for females. Having roommates who engage in similar internet entertainment was a risk factor for internet addiction only for males, while the absence of a romantic relationship was a risk factor for internet addiction only for females.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, respondents could select one of the following answers for each of the 10 items: never-−0, almost never-−1, sometimes-−2, fairly often-−3, very often-−4. The ranges of the total PSS-10 score indicated: low stress (0-13), moderate stress (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and high stress (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Accordingly, the higher the total score, the more severe the psychological distress.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 37 ], the social media usage amount reported by the study participants was dominant in predicting PIU, while the time spent on gaming did not predict PIU, which could be explained by the popularity and widespread use of social networking apps [ 36 , 38 ] but not gaming which requires larger screens and dedicated devices, relatively more expensive. Another study showed that time spent on gaming for males and online streaming for females were predictors of PIU [ 39 ]. A study in [ 40 ] found associations between PIU and gaming usage at night only, denoting conflict with other life priorities such as sleep.…”
Section: Introductionmentioning
confidence: 99%